The Prophetic Paradigm as a Legal Adaptive Strategy for Agricultural Extension Workers to Protect Food Agricultural Land in Singkawang City - Yuko Fitrian; Khudzaifah Dimyati; Absori; Arief Budiono; Said Saidakhrarovich Gulyamov (PT. Islamic Research Publiser, 2026)
This study addresses the gap between the normative objectives of Indonesia’s Sustainable Food Agricultural Land Protection Law and its implementation in practice, particularly in urbanizing areas such as Singkawang City, West Kalimantan. It examines how adaptive, non-formal implementation strategies can bridge this gap by placing farmer welfare at the center of policy implementation and using the Prophetic Social Science paradigm as an analytical lens. Accordingly, the study asks how an adaptive approach to socializing sustainable food crop land protection policies, grounded in farmer welfare and prophetic values, can reconcile formal regulations with the social realities of farming communities in Singkawang City. The study employs a qualitative case study approach, with data collected through interviews, observations, and document analysis. The data are analyzed using the street-level bureaucracy framework alongside three core prophetic values: humanization, liberation, and transcendence. The findings indicate that a formal, predominantly procedural approach is insufficient, as local governments operate under significant structural and institutional constraints. Instead, implementation becomes more effective through adaptive strategies developed by Field Agricultural Extension Workers. These strategies involve building social capital and trust through a humanistic approach and by providing concrete incentives that directly address farmers’ needs. Such practices reflect the prophetic value of liberation, helping farmers navigate and reduce the structural pressures that might otherwise undermine policy implementation. Academically, this study contributes to the street-level bureaucracy literature by demonstrating that non-formal and adaptive approaches inspired by prophetic values can enable street-level bureaucrats to translate state policies into meaningful social practices. It further shows that such approaches can strengthen government legitimacy by ensuring that policy implementation remains responsive to the lived realities and welfare needs of local communities.